PROTOTYPE PEMBANGKIT MIKROHIDRO TERINTEGRASI BEBAN KOMPLEMEN - Handry Setya Utama; Medilla Kusriyanto (Teknoin, 2018)
Electrical needs in industry as well as in households is one of the main needs as a source of energy for electrical devices. Currently the development of new and renewable energy sources and research involving many found in the world, one of which is a microhydro power plant. Indonesia is a country that has a stream that can be used as a source of energy, especially as a small scale power generator or often called microhydro. In this study the authors try to make a prototype microhydro power plant by utilizing used washer motor driver as a generator. The prototype is equipped with a complement load of inductors to maintain the stability of the voltage and frequency of the generator output when there is loading. The prototype also features a voltage indicator panel, frequency, flow of water to the generator using arduino as its signal processing module. From the observation result obtained maximum output from generator is 90 Volt with frequency 123Hz with speed generator 308 RPM and water debit 127 mL / sec. The addition of complement load on the generator greatly affects the output of the generator during loading.